ARAKTERISTIKKEPEMIMPINAN KEPALASEKOLAH - Rohmat Rohmat (LPMPP Universitas Negeri Yogyakarta, 2007)
his research was focused on the leadership style of thehead-master of State Secondary School 2 Cilacap, the degree of thehead-master ability in doing the function as a manager, educator,and leader, as well as the leadership effectiveness.This research used qualitative-naturalistic method.research subject consistedof school personnel of State SecondarySchool 2 Cilacap. The data was collected using interview technique,observation, and documentation. The data validity was achievedwith external and internal criticism and triangulation method. Thedata analysis technique was performed using Miles and Hubermanmodel, done in four interactive steps: data collection, data reduction,data display, and conclusion.The research result can be reported as follows :1) the headmasterof State Secondary School 2 Cilacap tends to adoptparticipative leadership style; 2.a) Concerning level of ability, indoing his function as a manager, it can be concluded that themanagerial functions (planning, organizing and controlling) havebeen done effectively. But on the staffing side, especially on studentrecruitment planning improvement is still seriously needed; b) Thehead - master has done his function as a leader. c) Furthermore, thehead-master has done supervision functionas a leader; d) the head master has shown good behaviour and can be a role model; 3) Thehead-master leadership effectiveness has been achieved by teacher:empowerment in the improvementof instructional process asindicated by graduates quality improvement.